Complete Genome and Plasmids Sequences of a Clinical Proteus mirabilis Isolate Producing Plasmid Mediated NDM-1 from Italy - Bitar, Ibrahim; Mattioni Marchetti, Vittoria; Mercato, Alessandra; Nucleo, Elisabetta; Anesi, Adriano; Bracco, Silvia; Rognoni, Vanina; Hrabak, Jaroslav; Migliavacca, Roberta (Microorganisms, 2020)
Background: The spread of carbapenemase genes, such as blaNDM-1, in Proteus mirabilis poses a public health threat. The aim of the study was to characterize the genome and plasmids sequences of an NDM-1-positive strain (IBCRE14), which was isolated in 2019 from a catheterized patient hospitalized in Italy. Methods: Whole genome sequencing (WGS) of IBCRE14 was performed on extracted genomic DNA using Sequel I platform. Genome assembly was performed using "Microbial Assembly". Genomic analysis was conducted by uploading the contigs to ResFinder and PlasmidFinder databases from the Center for Genomic Epidemiology. Results: IBCRE14 had a genome size of 4,018,329 bp and harboured genes coding for resistance to aminoglycosides (aadA1), phenicol (cat), tetracycline (tetJ), and trimethoprim (dfrA1). A large plasmid (pIB_NDM_1) harboured antibiotic resistance genes against sulphonamide (sul1), trimethoprim (dfrA14), tetracycline (tetB), rifampicin (arr-2), aminoglycosides (aadA1, aph3-VI), and beta-lactams (blaOXA-10, blaNDM-1). Furthermore, a small plasmid (pIB_COL3M) harboured a qnrD1 gene coding for quinolone resistance. Conclusion: The ability to conjugate and the presence of a composite antibiotic resistance island suggests that pIB_NDM_1 could both acquire more resistance genes and easily disseminate. To our knowledge, this is the first report on an untypable plasmid harbouring blaNDM-1 in P. mirabilis, in Italy.
Keywords: blaNDM-1; Proteus mirabilis; qnrD1